Portrayal of Filipino paralympians by selected local online news outlets during the Paris 2024 Paralympic Games - Agbugay, Karl Henry A.; Reyes, Patricia Maria R.
A substantial body of research has explored the media portrayal of Paralympians at the international level, but localized studies on the topic remain scarce. In the Philippines, where stigma and discrimination continue to pose significant challenges for the persons with disabilities (PWD) community, the need for ethical and inclusive reporting on disability, particularly in sports, has only become evident. This study seeks to contribute to the limited local literature by examining how selected online news outlets portrayed Filipino Paralympians during the Paris 2024 Paralympic Games. Grounded in De Vreese’s framing theory and employing a mixed-methods approach, this study analyzed communication artifacts, specifically sports articles published between August 12 and September 12, 2024, to identify the dominant and emergent frames in local Para sports journalism and assess the ethicality of media coverage. Semi-structured interviews were also conducted with six sports journalists to identify the different factors that influenced their reportage. Findings reveal that: 1) performance-based frames were among the most frequently employed by media; and 2) local coverage of the 2024 Paralympics generally adhered to international ethical standards for disability reporting. While a welcome development, the hyperfocus on performance underscores a need for broader exploration of other narratives that reflect the diverse lived experiences of Para athletes. Awareness of technical standards, especially in the use of appropriate terminology, can also still be enhanced within local newsrooms.